Mewujudkan Produk Unggulan Daerah Melalui Pelatihan Dan Pemasaran Nugget Bayam - Naila Fauza; Nicolich pengarapenta Purba; Ulfa Hasanah; Muhammad Bayu Pramana; Amalia Ilmia Sari; Jody Carverius Sidabuta; Kukuh Dinda Setiarani; Naily Syahratur Rahma; Chairunnisa Aulia Utami Harahap; Elviarni Elviarni; Rahmi Luthfiyyah AD (Unri Conference Series: Community Engagement, 2021)
As a village located in Kabun District, Rokan Hulu Regency, Giti Village has great potential in the agricultural sector. One of the dominant agricultural products is spinach as the village's superior product. However, the agricultural products are not processed further but are sent directly to the distributor. For this reason, in this article, we will discuss the development of superior products from Giti Village as an economic driver through education, training, and marketing of spinach nuggets. Education by conducting training; making spinach nuggets and training on making packaging labels. Producing and marketing spinach nuggets. The results of this community service are the creation of a productive and skilled community in making spinach nuggets and making packaging labels, the creation of people who can take advantage of technology in the 4.0 revolution era as an online marketing tool, and the formation of a spinach nuggets home business in Giti Village.